"We" are in This Pandemic, but "You" can get Through This: The Effects of Pronouns on Likelihood to Stay-at-Home During COVID-19. (October 2021) - Tu, Ke C.; Chen, Shirley S.; Mesler, Rhiannon M.
We examine how first-person plural and second-person singular pronouns used in coronavirus disease 2019 (COVID-19) communications impact people's likelihood to follow stay-at-home recommendations. A 2 (first-person plural ["we"] vs. second-person singular ["you"]) by continuous trait self-control between-subjects experiment ( N = 223) was used to examine individuals' adherence to stay-at-home recommendations. Results suggest that "you"-based appeals may be more broadly effective in garnering stay-at-home adherence, whereas low self-control individuals are less responsive to "we" appeals. Implications for research and practice are discussed.